1999
DOI: 10.1017/s1049023x00034567
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Scoring Systems Explained

Abstract: Abstracts: 11th World Congress, Osaka, Japan S79 with 42 femoral and 11 tibial fractures were treated with either reamed intramedullary nailing (Group R, n = 28) or with unreamed nailing (Group NR, n = 20) within three days of their injuries. The mean value for age was 27.4 years (range, 16 to 63 years). In Group R, 28 femoral and four tibial fractures, reaming was performed up to 12.5 mm, and a 9-11 mm nail was inserted. In Group NR, 14 femur and 7 tibial fractures, a 9-10 mm nail was inserted without reaming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…For instance, the term ''obtunded'', when used to describe a child, could be interpreted in a number of ways. Such vagueness lends itself to misinterpretation and inaccurate scoring [18,32]. Our univariate statistical analysis showed that the relation between PTS and mortality was not significant.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…For instance, the term ''obtunded'', when used to describe a child, could be interpreted in a number of ways. Such vagueness lends itself to misinterpretation and inaccurate scoring [18,32]. Our univariate statistical analysis showed that the relation between PTS and mortality was not significant.…”
Section: Discussionmentioning
confidence: 88%
“…Some of the previously published papers also showed increased levels of TNF-a and IL-1b early following injury [8,10,23,24]. The PTS, which is a simple and quick anatomic and physiologic scoring system, is the only one designed specifically to be applied to children, and reported to be developed to predict the survival of injured children [18,29]. Several reports have shown the validity of PTS to predict the severity of injury in those children in the most immediate danger of mortality [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, patient age is included for a more precise assessment of the probability of survival (Ps). 11 The coefficients were derived from the North American Major Trauma Outcome Study 1995.…”
Section: Datamentioning
confidence: 99%